The Empowerment Program On The Use Of Efficient Technology Of Coffee Processing In Wanagiri Bali - Ni Made Ayu Suardani Singapurwa; Aida Firdaus Muhammad Nurul Azmi; Fadhilah Lamun @ Jailani; Luh Suriati; Muhamad Hazim Bin Ahmad Nazari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The development of coffee-based agricultural businesses can improve the economy and welfare of people in rural and urban areas. Besides that, the increase in the coffee processing business also helps creating new jobs for the wider community. Village community empowerment was carried out to increase knowledge, attitudes, skills, behavior through activity programs and assistance according to the needs. One of the coffee-producing villages is Wanagiri Village, which is located in Sukasada District. The women of the Wanagiri village are members of the Family Welfare Program in Wanagiri Village which is engaged in coffee processing and helps their husbands as farmers. They asked to be given training and assistance regarding coffee food products to increase family income. Coffee is a product that is in great demand by people throughout Bali.Based on the demand, empowerment activities were carried out. Coffee products had been produced and marketed by partners but not yet intensively, and partners wanted to increase their quantity and quality. Partners did not have knowledge in the field of entrepreneurship, so they experienced obstacles in managing the production and marketing; moreover, they do not have a business license either. Solutions made to solve problems faced by partners were: Providing Appropriate Technology in processing coffee products; provide knowledge about good processing methods (GMP), sanitation and hygiene processing (SSOP), product packaging and labeling, broader marketing, entrepreneurship and business management. In addition, another solution was sharing knowledge on how to obtain a production permit and provide equipment assistance. The method used was active community participation and exploratory. The output achieved was the use of Appropriate Technology in Coffee Processing Technology.